2021
DOI: 10.1590/0037-8682-0519-2020
|View full text |Cite
|
Sign up to set email alerts
|

Early hematological parameters as predictors for outcomes in children with dengue in northern India: A retrospective analysis

Abstract: INTRODUCTION: Dengue presents with a variable clinical course, ranging from mild illness to potentially fatal hemorrhage and shock. We aimed to evaluate the capabilities of various hematological parameters observed early in the course of illness for predicting the clinical outcomes of illness. METHODS: We retrospectively analyzed the records of children admitted in the pediatric inpatient services of the institute with dengue between 2017 and 2019. We determined the rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 22 publications
2
12
0
1
Order By: Relevance
“…Similar observations were made by Mishra et al [7] and Majeed et al [13]. However, Nandwani et al [12] noted that severe dengue and complications were more in female children.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Similar observations were made by Mishra et al [7] and Majeed et al [13]. However, Nandwani et al [12] noted that severe dengue and complications were more in female children.…”
Section: Discussionsupporting
confidence: 76%
“…We observed that majority were from 5 to 10 years age group. This may be due to more outdoor activities by children of this age group and relatively more uncovered area and hence more prone for mosquito bites [9][10][11][12]. Male children (61.5%) were more commonly affected by dengue fever than female children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, this study shows that increased leukocyte counts indicate increased mortality in hospitalised patients with infection. Similar studies have shown that the death rate of patients with cancer and dengue increases with increasing leukocyte counts [ 41 , 42 ]. Infections destroy the dynamic balance of the immune system and cause significant changes in the neutrophil count, which are closely related to mortality [ 43 , 44 ].…”
Section: Discussionmentioning
confidence: 70%
“…Also, the patients who deteriorated later had mean TLC and PLT counts near the lower limit of normal at initial presentation compared to patients with DF who did not progress to SD. Similarly, high HCT and low PLT were reported to be significantly associated as risk factors in the febrile phase for progression to severe disease from recent systematic reviews and meta-analyses [ 17 , 19 ] and other studies [ 20 ]. Tachypnea as a significant factor in these patients could be because of high grade fever or early sign of fluid accumulation in this group as compared to the other group [ 3 ].…”
Section: Discussionmentioning
confidence: 93%